2012
DOI: 10.3109/00365599.2012.726644
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age and changes over time on erectile dysfunction: Results from two large cross-sectional surveys 11 years apart

Abstract: Despite a seemingly healthier lifestyle in 2003 compared with 1992, the rate of ED increased in the population, highlighting the importance of assessing lifestyle factors when examining ED patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 25 publications
(28 reference statements)
1
1
0
Order By: Relevance
“…Apart from weaker desire in older patients, we found that none of the three factors of patient age, time since diagnosis of MS, and EDSS score were independently correlated with the incidence or severity of SD. Age and age-related comorbidities have been confirmed as powerful predictors of ED in many studies [31][32][33]. The similar prevalence of ED across age groups in our research may be explained by neurological and psychosocial changes that appear in MS independently of age.…”
Section: Discussionsupporting
confidence: 83%
“…Apart from weaker desire in older patients, we found that none of the three factors of patient age, time since diagnosis of MS, and EDSS score were independently correlated with the incidence or severity of SD. Age and age-related comorbidities have been confirmed as powerful predictors of ED in many studies [31][32][33]. The similar prevalence of ED across age groups in our research may be explained by neurological and psychosocial changes that appear in MS independently of age.…”
Section: Discussionsupporting
confidence: 83%
“…The Health Professionals Follow-Up Study, a large cross-sectional study including 31,742 men, aged 53-90 years, found that smoking was associated with the risk of ED [73]. A further survey of 10,458 men living in Gothenburg, Sweden, in 1992 revealed that smoking most significantly affected the risk of ED along with concomitant medication use [74]. Cao et al conducted a metaanalysis involving 28,586 participants to evaluate the association between smoking and the risk of ED [75].…”
Section: Smokingmentioning
confidence: 99%